Physicians' Mental Health Conditions at Medical College Hospitals during the COVID-19 Pandemic (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2025)
Background: The Coronavirus Disease (COVID-19) outbreak in 2019 had a psychological impact on almost everyone, including medical personnel who work mostly in hospitals. Physicians faced incredible levels of workload, which exacerbated many mental health issues in this circumstance. The purpose of the study assess the mental health conditions of physicians at the purposively selected four Medical College Hospitals in Dhaka city. Materials and methods: During the outbreak of COVID 19 in Bangladesh, a hospitalbased cross-sectional study was carried out during the period January to July 2021. ‘The Depression, Anxiety, and Stress Scale-21’ (DASS-21) scale was used to construct this semi-structured questionnaire for data collection during the study period. Results: In terms of the physicians' mental health state, one-fourth (25.9%) had extremely severe depression, one-third (36.0%) had extremely severe anxiety and one-quarter (21.8%) experienced severe stress. It was found that doctors who were married, older and had an average monthly income of £50,000 BDT were more likely to experience depression. Additionally, there was a significant increase in depression among private hospital employees, who also reported feeling stigmatized by their profession and inadequate Personal Protective Equipment (PPE) at work. Doctors who were married, older, and had an income of £50,000 BDT were found to have higher levels of anxiety. Additionally, there was a significant rise in anxiety among private hospital employees, who also reported feeling stigmatized by their profession and having inadequate PPE. Ageing older and having an income of £50,000 BDT were found to be associated with higher levels of stress. Inadequate PPE in the workplace, the stigma associated with one's job and employment in private hospitals were all associated with substantially higher stress levels. Conclusion: In Bangladesh, a significant proportion of doctors experienced anxiety, stress, and depression during the COVID-19 outbreak. To reduce instances of stress, anxiety, and depression in doctors, effective strategies are needed in their workplaceChatt Maa Shi Hosp Med Coll J; Vol.23 (2); July 2024; Page 53-59